Genome‐Wide Association Study Identifies Risk Loci for Cluster Headache. Issue 2 (14th July 2021) - O'Connor, Emer; Fourier, Carmen; Ran, Caroline; Sivakumar, Prasanth; Liesecke, Franziska; Southgate, Laura; Harder, Aster V. E.; Vijfhuizen, Lisanne S.; Yip, Janice; Giffin, Nicola; Silver, Nicholas; Ahmed, Fayyaz; et al.
Abstract : Objective: This study was undertaken to identify susceptibility loci for cluster headache and obtain insights into relevant disease pathways. Methods: We carried out a genome‐wide association study, where 852 UK and 591 Swedish cluster headache cases were compared with 5, 614 and 1, 134 controls, respectively. Following quality control and imputation, single variant association testing was conducted using a logistic mixed model for each cohort. The 2 cohorts were subsequently combined in a merged analysis. Downstream analyses, such as gene‐set enrichment, functional variant annotation, prediction and pathway analyses, were performed. Results: Initial independent analysis identified 2 replicable cluster headache susceptibility loci on chromosome 2. A merged analysis identified an additional locus on chromosome 1 and confirmed a locus significant in the UK analysis on chromosome 6, which overlaps with a previously known migraine locus. The lead single nucleotide polymorphisms were rs113658130 ( p  = 1.92 × 10 −17, odds ratio [OR] = 1.51, 95% confidence interval [CI] = 1.37–1.66) and rs4519530 ( p  = 6.98 × 10 −17, OR = 1.47, 95% CI = 1.34–1.61) on chromosome 2, rs12121134 on chromosome 1 ( p  = 1.66 × 10 −8, OR = 1.36, 95% CI = 1.22–1.52), and rs11153082 ( p  = 1.85 × 10 −8, OR = 1.30, 95% CI = 1.19–1.42) on chromosome 6. Downstream analyses implicated immunological processes in the pathogenesis of cluster headache. Interpretation: We identified and replicated several genome‐wide significant associations supporting a genetic predisposition in cluster headache in a genome‐wide association study involving 1, 443 cases. Replication in larger independent cohorts combined with comprehensive phenotyping, in relation to, for example, treatment response and cluster headache subtypes, could provide unprecedented insights into genotype–phenotype correlations and the pathophysiological pathways underlying cluster headache. ANN NEUROL 2021;90:193–202